Health status assessment of workers during construction phase of highway rehabilitation projects around lahore, Pakistan. Issue 1 (24th January 2017) - Abrar, Amina; Cheema, Kausar Jamal; Saif, Samia; Mahmood, Asim
Abstract : Objective: The study focused on assessment of the health status of workers during construction phase of highway rehabilitation projects at six selected sites of N5 around Lahore, including Kala Shah Kaku, Muridke, Kamuki, Bhaipheru, Pattoki, and Okara. Methods: The study was based on multi‐methods approach involving hazard identification through survey and checklist as well as a questionnaire for health status assessment and measurements of health parameters including peak expiratory flow rate (PEFR) and audiometric screening of 300 subjects. Results: The study revealed non‐congenial working conditions at the sites. Noise, vibrations, dust, asphalt fumes, poor work postures, and injuries were found to be major health hazards. PEFR of most of the workers was found to be significantly lower than the reference value. Average PEFR±SEM values were 187± 5.1 l /min, 178±4.3 l/min, and 266±5.3 l /min in ground preparation workers, asphalt workers, and heavy vehicle drivers, respectively. The highest rate (29%) of hearing loss was recorded among heavy vehicle drivers. Musculoskeletal problems were found to be more common among ground preparation workers. Conclusion: Data revealed unsatisfactory health status of most of the workers. Direct relationship between health outcomes and the type of construction activities were observed. The current study focuses on the importance of including occupational health and safety plan in the execution phase of every developmental project that involves construction activities.